Blasphemy Laws and Female Vulnerability in Northern Sharia States in Nigeria - Mpigi, Goka Muele; Koko, John Clerk (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
This paper examines the intersection of religion, gender, and justice in Northern Sharia states in Nigeria. It investigates how patriarchal interpretations of Islamic law and weak state institutions combine to expose women to mob violence, extrajudicial killings, and systemic discrimination. Using the methodology of desk-based analysis, the research explains how four theoretical frameworks: liberal, radical, intersectional and vulnerability feminist theories reveal the risk faced by the female gender in highly patriarchal context. The research also explains how law, culture, and faith interlock to sustain gendered oppression. Juxtaposing this with empirical evidence drawn from documented cases between 1999 and 2025, the work reveals that accusations of blasphemy serve as instruments of control over women’s expression and moral autonomy. The study finds that moral absolutism, theological distortion, and legal pluralism have collectively eroded justice and human dignity. It concludes that safeguarding women’s rights requires harmonizing religious and constitutional laws, strengthening gender-responsive justice systems, promoting interfaith moral education, and institutionalizing accountability mechanisms. Ultimately, the research calls for a renewed moral and legal consciousness where faith coexists with freedom, and the sanctity of human life becomes the truest expression of religion. Keywords: Blasphemy laws, Female vulnerability, Northern Sharia states, and Nigeria.